Application of the Method of Providing Nursing Care with a Patient Care Center in a Kupang Private House - Janwar Olang; Natya Paluwih; Elisabeth Sinulingga; Erlinda Bunga (Indonesian Journal of Contemporary Multidisciplinary Research, 2022)
Nursing is a form of professional service in the form of meeting basic needs given to healthy and sick individuals who experience physical, psychological and social disorders in order to obtain optimal health status. There are various models of providing nursing care that are carried out. The professional nursing care model system consists of: functional method, team method, primary method, case method, and primary team method. Writing this scientific report is to find out about the application of a model of providing professional nursing care with a patient care center in a private hospital in Kupang. This research uses a descriptive quantitative method. The sample in the study was 25 respondents, consisting of 10 PCAs and 15 nurses. The instrument used was a questionnaire in the form of a Likert scale by giving a checklist